Legal Disparities in Unregistered Polygamous Marriages from the Perspective of Justice and Child Welfare: A Philosophical Examination - Didi Jubaidi; Khoirunnisa Khoirunnisa (Fakultas Hukum, 2025)
Unregistered polygamous marriages (poligami siri) often give rise to complex legal issues, particularly regarding the protection and rights of children. The disharmony between positive legal norms and social realities creates legal disparities that result in uncertainty over the legal status of children born from such marriages. This situation leads to a central legal inquiry: How can the formulation of legal norms be directed to ensure the protection of children’s rights in the context of unregistered polygamous marriages? This study aims to analyze these legal gaps through a philosophical approach, emphasizing the principles of justice and child welfare. Using a qualitative method through literature review, this paper reflects on the values of substantive justice that should underpin legal formulation and implementation. The findings indicate that the existing legal framework does not fully guarantee the protection of children's rights in the context of unregistered polygamy. Therefore, a reformulation of legal norms is necessary one that is more responsive to social realities and aligned with justice and welfare principles as the philosophical foundation of law.